Analisis Nilai Tambah Dan Pemasaran Olahan Buah Mangrove - Kurniawan, Ari; Nurcahyani, Marizha (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
The processing of mangrove fruits into food products such as dodol, syrup, chips, and tea is a strategy to increase the economic value and welfare of coastal communities. This literature review aims to analyze the added value of various processed mangrove fruit products and evaluate their marketing strategies. This study uses the literature review method, which is a method conducted by collecting, analyzing, and synthesizing various relevant literature sources related to the research topic. The purpose of this method is to understand the analysis of added value and marketing of processed mangrove fruit products, identify research gaps, and formulate a conceptual framework that supports the discussion. The data analysis method is carried out through an analytical process that begins with qualitative and descriptive dataThe study findings indicate that the added value ratio of processed mangrove products is relatively high, ranging from 50% to 91%, depending on the type of product and the processing location. However, the marketing of these processed products remains suboptimal, mostly conducted during events or tourist visits. Recommended marketing strategies include the use of social media, branding training, and improving the community’s digital skills. With proper processing and marketing, mangrove fruits have the potential to become a sustainable alternative source of income for coastal communities.